Reduced heart rate variability in chronic severe traumatic brain injury: Association with impaired emotional and social functioning, and potential for treatment using biofeedback. Issue 1 (2nd January 2016) - Francis, Heather M.; Fisher, Alana; Rushby, Jacqueline A.; McDonald, Skye
Abstract : Heart rate variability (HRV) may provide an index of capacity for social functioning and may be remediated by HRV biofeedback. Given reductions in HRV are found following traumatic brain injury (TBI), the present study aimed to determine whether lower HRV in TBI is associated with social function, and whether HRV biofeedback might be a useful remediation technique in this population. Resting state HRV and measures of social and emotional processing were collected in 30 individuals with severe TBI (3–34 years post-injury) and 30 controls. This was followed by a single session of HRV biofeedback. HRV was positively associated with social cognition and empathy, and negatively associated with alexithymia for the TBI group. Both TBI and control groups showed significantly increased HRV on both time-domain (i.e., SDNN, rMSSD) and frequency-domain measures (LF, HF, LF:HF ratio) during biofeedback compared to baseline. These results suggest that decreased HRV is linked to social and emotional function following severe TBI, and may be a novel target for therapy using HRV biofeedback techniques.